Diagnosis In The Ordinal Logistic Regression Model - Rasheed, Noha M (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The relationship between one or more of the explanatory variables and the ordinal categorical response variable is described as "Ordinal logistic regression (ORS) models." The quality of the fit for the model must be checked when the regression model has been adjusted. Chi-square and probability ratio statistics of Pearson are insufficient to evaluate the suitability of the standard logistic regression model when the model has continuous variables. In the current issue, the diagnostic techniques like Lipsitz tests and other variables were used to determine the relationship between the No Income, minimum wage, and emotional issues in elderly people were applied to Cumulative logite models, Logit adjacent classes, and Logit continuous reason patterns.